Pemicuan Sanitasi Total Berbasis Masyarakat Di Desa Buluh Cina Kecamatan Siak Hulu Kabupaten Kampar - Zahtamal Zahtamal; Fachriani Putri; Fifia Chandra; Ridha Restila (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
At present, the behavior of Indonesian people, including in the village of Buluh Cina, is still widely accustomed to Open Defecation (OD), especially to rivers that are also used for washing, bathing and other hygienic needs. This community service activity has been carried out with the aim of helping to solve the problem of open defecation through community lead total sanitation (CLTS). The main target in this community service is people who still behave OD or do not have healthy latrines. In addition, other targets are health workers from the Siak Hulu Tiga Health Center and Buluh Cina village officials who will provide long-term guidance and supervision of the CLTS movement. Techniques / strategies for solving problems in community service activities are collecting data in the form of surveys and interviews and facilitating each CLTS triggering activity, as well as evaluating the success of interventions. This activity has been able to provide benefits to various parties, including the Department of Health, local government, health workers at the Puskesmas and especially the community that has carried out CLTS activities. Based on this CLTS triggering activity, there has been an increase in understanding and awareness of the importance of open defecation free (ODF) behavior and the importance of family healthy latrine ownership.